2023
DOI: 10.1021/acs.jpcc.3c01396
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Dissolved Transition Metals in Battery Electrolyte Solutions with NMR Paramagnetic Relaxation Enhancement

Abstract: Transition metal dissolution is an important contributor to capacity fade in lithium-ion cells. NMR relaxation rates are proportional to the concentration of paramagnetic species, making them suitable to quantify dissolved transition metals in battery electrolytes. In this work, 7Li, 31P, 19F, and 1H longitudinal and transverse relaxation rates were measured to study LiPF6 electrolyte solutions containing Ni2+, Mn2+, Co2+, or Cu2+ salts and Mn dissolved from LiMn2O4. Sensitivities were found to vary by nuclide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…The 1 H NMR and 19 F NMR spectra of the electrolytes collected after the powd ing test (shown in Figure 6a,b, respectively) displayed similar peaks shifting and ening with an order of LNMO (Targary or NEI Corporation) > LMO > NMC442 NMC/NMC811. The ICP-MS data (Figure 7) were also plotted in this order, an crease in Mn dissolution content was observed along this order, further demon that the NMR peaks shifting and broadening was caused by the paramagnetic M solution [13,14]. Based on the results from NMR and ICP-MS measurements, i concluded that compared to layered structure NMC, spinel LNMO and LMO much more severe Mn dissolution when in contact with the carbonate-based ele This indicates that the electrode/electrolyte interaction for LNMO was harshe could explain the delamination issue observed in its high-voltage cycled cells.…”
Section: Gen2 Soaking With Different Tmo Powdersmentioning
confidence: 85%
“…The 1 H NMR and 19 F NMR spectra of the electrolytes collected after the powd ing test (shown in Figure 6a,b, respectively) displayed similar peaks shifting and ening with an order of LNMO (Targary or NEI Corporation) > LMO > NMC442 NMC/NMC811. The ICP-MS data (Figure 7) were also plotted in this order, an crease in Mn dissolution content was observed along this order, further demon that the NMR peaks shifting and broadening was caused by the paramagnetic M solution [13,14]. Based on the results from NMR and ICP-MS measurements, i concluded that compared to layered structure NMC, spinel LNMO and LMO much more severe Mn dissolution when in contact with the carbonate-based ele This indicates that the electrode/electrolyte interaction for LNMO was harshe could explain the delamination issue observed in its high-voltage cycled cells.…”
Section: Gen2 Soaking With Different Tmo Powdersmentioning
confidence: 85%
“…However, there are a few factors that the user should be aware of. First, large amounts of transition metal dissolution, particularly dissolved Mn 2+ , can broaden NMR signals, making it difficult to detect electrolyte decomposition products . Second, the presence of HF in LiPF 6 -based solutions requires that the cell be placed into a chemically resistant NMR tube as mentioned above.…”
Section: Tracking Decomposition At the Cathode/electrolyte Interface ...mentioning
confidence: 99%
“…20 Later simulations of the Mn 2+ solvation shell showed that Mn 2+ interaction energies follow the order EC > PF 6 − > linear carbonates. 21 Our previous NMR studies have suggested that dissolved transition metals may favour coordination to EC over ethyl methyl carbonate 22,23 and may coordinate preferentially to PF 6 − degradation products over pristine electrolyte components. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the presence of dissolved paramagnetic ions can result in differential enhancement of the NMR relaxation rates of the signals from a variety of species in both pristine and degraded battery electrolyte solutions. 23,24 We have used these relaxation rates, coupled with the accompanying bulk magnetic susceptibility shifts, to quantify metal concentrations and investigate binding to different electrolyte solvents. We have also used EPR to, for example, establish the solvation shell of dissolved vanadyl ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation